FORMULATION AND STABILITY EVALUATION OF ATENOLOL GEL IN TWO DIFFERENT BASES - CHAERUNISAA, ANIS YOHANA; MITA, SORAYA RATNAWULAN; RAHMAT, DEWI DAILAH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the research about atenolol gel is to formulate and evaluate its stability in hydroxypropyl methylcellulose (HPMC) and Aqupec HV-505 gel base. Methods: Gels were formulated using Acupev HV-505 and HPMC at three different concentrations. Physicochemical evaluation and stability testing were performed including organoleptic examination, pH, viscosity, consistency, bleeding, qualitative analysis by thin-layer chromatography (TLC), and quantitative analysis by UV-visible spectrophotometry during 56 days of storage. Results: Physicochemical evaluation showed that the best formula was the one with 1% Aqupec HV-505 base (FA2). Further investigation was conducted by varying atenolol concentration to study the influence on gel stability. Evaluation on organoleptic performance, pH, viscosity, consistency, bleeding, microbiology, and qualitative and quantitative stability testing using TLC and UV-visible Spectrophotometry during 56 days of storage showed that the best gel formula was FA22, the one using 1% Aqupec HV-505 with 0.5% Atenolol The patch test showed that all atenolol gels were safe to be used. Conclusions: About 1% Aqupec HV-505 provided good physical properties and physicochemical stability to be used as gel base.